Real-time disk scheduling for multimedia applications with deadline-modification-scan scheme - Chang, RI; Shih, WK; Chang, RC (My University, 2000)
Real-time disk scheduling (RTDS) is important for time-critical multimedia applications. In conventional approaches of real-time disk scheduling, such as SCAN-EDF, the seek-optimizing SCAN scheme is applied to reduce the disk service time of the real-time EDF schedule. Since only tasks with the same deadline are seek-optimized, the obtained improvement of SCAN-EDF is limited. In this paper, based on the maximum-scannable-group (MSG) concept, a deadline-modification-scan (DMS or DM-SCAN) algorithm is proposed. Our algorithm uses MSG to automatically decide the suitable task groups for seek-optimizing. Based on the MSG concept, we repeatedly apply DMS to further increase disk throughput to support more tasks. We have implemented the proposed algorithm on UnixWare 2.01. The appropriate problem behaviors and parameter values to yield good solutions are investigated. Experiments show that DMS is better than conventional approaches in both the obtained disk throughput and the supported tasks. Moreover, our proposed approach can schedule task sets that are not schedulable by EDF and SCAN-EDF.
Keywords: RTDS (real-time disk scheduling); multimedia applications; SCAN; EDF (earliest-deadline-first); operating systems; maximum-scannable-group (MSG); deadline-modification-scan (DMS)